BAY' AL-TAWARRUQ DAN APLIKASINYA DALAM PEMBIAYAAN PERIBADI DI BANK ISLAM MALAYSIA BERHAD - Ab Rahman, Asmak; Mohamad, Shamsiah; Mohd Salleh, Iman (Jurnal Syariah, 2019)
Bay' al-tawarruq is a Shariah contract used in forming Islamic financial products nationally or internationally. Most of the Islamic finance products used tawarruq munazzam. This article will discuss the concept of bay` al-tawarruq, the opinion of the Muslim scholars on tawarruq and a comparison between bay` al-`'inah dan al-tawarruq. This article will also discuss how bay` al-tawarruq has been implemented in the personal financing products in Bank Islam Malaysia Berhad.